Islamic Education in Cyberspace: An Analysis of Intellectual Humility in Gus Baha' Lectures on the Youtube Platform - Wahyudi, Winarto Eka; Alanshori, Zainuddin (Al-Hayat: Journal of Islamic Education, 2023)
The flow of information on the internet, including religious narratives, is currently impossible to avoid. This article discusses understanding Islam with intellectual humility for virtual society to live up to religious teachings with tolerance, moderation, and mutual respect. This study gathered data from documentation of Gus Baha's recitation, which is widely distributed on the YouTube social media platform. This study used a qualitative-descriptive research method and a netnographic analysis model. This method uses a particular analytical technique offered, AMS (Siber Media Analysis), which goes through 4 levels: Media room level, media document level, media object level, and experience level. This study was successful in determining that Gus Baha's intellectual humility is built on two things: first, a thorough understanding of Islamic teachings (khatam), and second, the belief that humans cannot act like God by enforcing laws against humans in the context of reality, which can change at any time. Furthermore, online media-based Islamic education can be accessed in real-time, stipulating that those presenting Islamic teachings in online media be mature figures, both intellectually and emotionally, as well as socially sensitive in a multicultural society.